Implementation of Muhadharah Activities to Train the Speaking Skills of Female Students at the Baitul Arqom Islamic Boarding School Balung, Jember - Budiati Cahyani; Romli A. Muchit; Syamsul Anam (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
Muhadharah activities at the Baitul Arqom Islamic Boarding School for female students are one of the mandatory activities that female students must participate in from grade one to grade five. The languages used for communication and during muhadharah activities are Arabic, English and Indonesian. Maharah kalam is the skill of conveying messages verbally to others. The purpose of this study is: To determine the implementation of muhadharah activities in speaking skills training at the Baitul Arqom Islamic Boarding School in Balung Jember and to determine the importance of muhadharah activities in training speaking skills at the Baitul Arqom Islamic Boarding School in Balung Jember. This study: uses a qualitative approach, with a descriptive type, and data collection methods through observation, interviews and documentation, and analyzes them based on the theory of Mills and Huberman, namely data openness, presentation and conclusions. Data validity is based on source triangulation and technical triangulation. The results of this study: (1) The implementation of muhadharah activities in the training of maharah kalam for female students at the Baitul Arqom Balum Jember Islamic boarding school, namely Muhadharah activities are carried out once a week, namely Thursday and Friday evenings. This activity is divided into 8 groups in which there are 29-31 female students and 5-6 correctors. While the method used in muhadharah activities is the memorization method. And at the end of each muhadharah, the Islamic boarding school holds an inter-class competition where the competition includes a 3-language muhadharah competition, a language debate competition, and a 3-language drama which aims to increase maharah kalam. (2) The importance of muhadharah activities in training speaking skills for female students at the Baitul Arqom Balung Jember Islamic boarding school is to foster self-confidence, train skills in front of people, get used to speaking in front of people, and train fluency in speaking, fluency in foreign languages.